2014
DOI: 10.1631/jzus.b1300239
|View full text |Cite
|
Sign up to set email alerts
|

Stability and cytotoxicity of angiotensin-I-converting enzyme inhibitory peptides derived from bovine casein

Abstract: This study investigated the effect of heat treatment combined with acid and alkali on the angiotensin-Iconverting enzyme (ACE) inhibitory activity of peptides derived from bovine casein. The free amino group content, color, and cytotoxicity of the peptides were measured under different conditions. When heated at 100 °C in the pH range from 9.0 to 12.0, ACE inhibitory activity was reduced and the appearance of the peptides was significantly darkened. After thermal treatment in the presence of acid and alkali, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Thus, bioactivity may diminish or be lost (Bloom et al 2015). In agreement with research by Wu et al (2014), this work suggested that hydrolysates with ACEIA could be stable in the heat and time treatments of food processes carried out in temperatures ranging from 60 to 100°C and also for short periods of time. In a study by Hwang (2010) peptides derived from tuna cooking juice proteins retained ACEIA.…”
supporting
confidence: 84%
See 3 more Smart Citations
“…Thus, bioactivity may diminish or be lost (Bloom et al 2015). In agreement with research by Wu et al (2014), this work suggested that hydrolysates with ACEIA could be stable in the heat and time treatments of food processes carried out in temperatures ranging from 60 to 100°C and also for short periods of time. In a study by Hwang (2010) peptides derived from tuna cooking juice proteins retained ACEIA.…”
supporting
confidence: 84%
“…Peptide fractions of hydrolysates (80 g/l) were separately adjusted to pH 4.0 and 7.0 with buffer solution and heated (40, 60, 80, 100 and 120°C) for 1 h. The pH effect on bioactivity of hydrolysates was assessed using various buffer solutions at different pH values (1.0, 2.0, 3.0, 4.0, 5.0, 6.0, 7.0, 8.0, 9.0, 10.0, 11.0, and 12.0), which were heated at 100°C for 1 h. To investigate the effect of the duration of heat treatment, peptide solutions were adjusted to pH 4.0 or 7.0 and incubated at 100°C for 1.0, 2.0, 3.0, or 4.0 h. Unheated peptide fractions were used as control (Wu et al 2014). …”
Section: Stability Of Bioactive Peptides As Influenced By Physical Anmentioning
confidence: 99%
See 2 more Smart Citations
“…However, when the hydrolysates were heated above 100 ∘ C, the ACE inhibition rate significantly decreased. When compared to that of the control group, the ACE inhibitory activity decreased by 20.50% at 120 ∘ C. Extreme heating or sterilization may result in the decrease of ACE inhibitory activity due to loss of some available peptides [66,67]. Furthermore, the C-terminal residues strongly influence the ACE inhibition and it is also enlarged by the presence of the +ve charge lysine and arginine as C-terminal residue.…”
Section: Effect Of Ultrasound Pretreatment On Solubility Of Rapeseed mentioning
confidence: 98%